Effect of Dreall Healthy about Sedentary Life Style for Increasing Motivation to Children with Obesity - Fuji Rahmawati; Dwi Septiawati; Firnaliza Rizona (Faculty of Public Health, Hasanuddin University, Makassar, 2021)
The Increasing prevalence of children with obesity was showed in all around the world include in Indonesia. The dominant factor was a sedentary life style and lack of activity. Those habits would be made the energy being unused so the fat will be accumulation become obesity. This Study aimed to know the effect of dreall healthy sedentary lifestyle on obese school-age children. This research was used pre-experimental with one group pre posttest design to analyze the data about motivation. The number of was 60 school-age children with obesity in Palembang city the data collected by using questioner after arranging the puzzle that was a development based on the collected data. The statistic result with Wilcoxon test showed improving motivation with the result p=0,001. Fun education might become one method for increasing motivation on children to raise their physics activity.